PEMAHAMAN KODE ETIK PROFESI AKUNTAN ISLAM DI INDONESIA - Pravitasari, Dyah (IAIN Tulungagung, 2015)
This study has the aim of providing an overview of the accounting profession of Islam in Indonesia and provide an explanation of the code of ethics of Islam accountant . Code of Conduct accountant Islam basically consists of aspects of Sharia as the basic principles of the code of ethics accountants, for accountants ethical principles, and ethical behavior for regulation of accountants. Islam has a system of accounting which refers to the Qurâan and Sunnah and has been practiced in the early days of Islam until the rise of the Islamic Caliphate. This system has a lot in common with an accounting system that has been used at the present time, so when viewed from the historical side, many people in Europe learn from Islamic countries and have adopted knowledge including accounting. Code of Conduct by AAOIFI Islamic accountants includ: trustworthiness, legitimacy, objectivity, competence and diligent professi, behavior and behavior faith driven professional and technical standards.Keywords: Principles of ethics for accountant , Regulation of ethical conduct for accountants and Code of Conduct